Implication of Albumin, Microalbumin and Alpha-Feto Protein Variation in Preeclamptic Pregnant Women in the Third Trimester of Pregnancy - Edebiri O.E; Akpe C. I.; Onwuka K. C.; Ehigiamusoe A. O.; Okike P.I.; Ohiwerei W.O.; Nze P.O (Lembaga Pengembangan Kinerja Dosen, 2025)
The presence of Albumin, Microalbumin and Alpha-Feto Protein increase activity in third trimester. The aims of this study is to determine the Implication of Albumin, Microalbumin and Alpha-Feto Protein Variation in preeclamptic pregnant women in the third trimester of pregnancy. Forty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. Blood samples was spun in a bucket centrifuge at 2500 RPM (rounds per minute) for 10 minutes after which plasma was collected and stored frozen in plain sample bottles and was analyzed for liver enzymes (albumin, Microalbumin and Alpha-fetoprotein) levels by fluorescence immunoassay method. . Data obtained from this study were analysed using Graph Pad Prism 9. Results generated were expressed as mean ± SEM and a P-value of ≤ 0.05 were considered statistically significant. The present study showed that there was statistically significant increase in Albumin, Micro albumin were observed in preeclamptic women compared to normotensive pregnant women, indicating various underlying pathophysiological processes such as liver dysfunction. These findings suggest albumin and Micro albumin are implicated as potential biomarkers in identifying and monitoring preeclampsia. However, levels of alpha-fetoprotein (AFP) did not show significant differences between preeclamptic and normotensive women.